THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN GRAN PURI HOTEL MANADO - Yosep, Canalini (Sam Ratulangi University, 2016)
ABSTRACT This research was conducted in Hotel Gran Puri Manado on July to Augustus 2014. Hotel Gran Puri Manado is one hotel in Manado city, North Sulawesi Province and becomes one developed city in Indonesia. The study aims to analyze the service quality dimensions (Tangibility, Reliability, Responsiveness, Assurance, and Empathy) influence customer satisfaction in Hotel Gran Puri Manado. The research population is the people who experiences stayed at Hotel Gran Puri Manado. 40 customers of Gran Puri Hotel Manado were surveyed as samples. Data analysis was Multiple Regression Analysis. The result shows; Tangibility, Reliability, Responsiveness, Assurance and Empathy simultaneously are significant influence to customers satisfaction. Although, Tangibility, Reliability, Responsiveness, Assurance and Empathy partially are significant influence to customers satisfaction. Keywords: Service Quality, Customer Satisfaction.